Survey of major load balancing algorithms in distributed system - Radivilova, T.; Ivanisenko, I. (My University, 2015)
The classification of the most used load balancing algorithms in distributed systems (including cloud technology, cluster systems, grid systems) is described. Comparative analysis of types of the load balancing algorithms is conducted in accordance with the classification, the advantages and drawbacks of each type of the algorithms are shown. Performance indicators characterizing each algorithm are indicated. The most used load balancing algorithms of distributed systems are classified according to different types in this work. Based on the performed analysis of classification types of the load balancing algorithms the scope of each type of algorithms is indicated, the algorithms types necessary operation requirements are defined, defaults of each type of algorithms are shown. In this way one can select a particular type of the load balancing algorithm based on the specifics of a particular project or executable task, and the goals to be achieved. The description of the main features of load balancing algorithms, analysis of their advantages and defaults are also presented in this work. A comparative analysis of different load balancing algorithms on various performance metrics is carried out, i.e., the efficiency indicators are shown for each algorithm used in it. It is planned to realize a comparative analysis of the load balancing algorithms with different capacity in a variety of distributed systems: cloud, cluster and grid systems.
Keywords: distributed system; load balancing algorithm; distributed system; throughput; resource utilization; capacity